Origins and Early Evolution of the tRNA Molecule - Koji Tamura (Life, 2015)
Modern transfer RNAs (tRNAs) are composed of ~76 nucleotides and play an important role as “adaptor” molecules that mediate the translation of information from messenger RNAs (mRNAs). Many studies suggest that the contemporary full-length tRNA was formed by the ligation of half-sized hairpin-like RNAs. A minihelix (a coaxial stack of the acceptor stem on the T-stem of tRNA) can function both in aminoacylation by aminoacyl tRNA synthetases and in peptide bond formation on the ribosome, indicating that it may be a vestige of the ancestral tRNA. The universal CCA-3′ terminus of tRNA is also a typical characteristic of the molecule. “Why CCA?” is the fundamental unanswered question, but several findings give a comprehensive picture of its origin. Here, the origins and early evolution of tRNA are discussed in terms of various perspectives, including nucleotide ligation, chiral selectivity of amino acids, genetic code evolution, and the organization of the ribosomal peptidyl transferase center (PTC). The proto-tRNA molecules may have evolved not only as adaptors but also as contributors to the composition of the ribosome.